INSTRUKSI KONTROL PLAK DAN SKALING SEBAGAI METODE PERAWATAN GINGIVITIS PUBERTAS PADA SANTRI PONDOK PESANTREN - Da’at Arina, Yuliana Mahdiyah (FKM - UNEJ, 2009)
The prevalence of gingivitis increased in the puberty periods (Puberty gingivitis). Most of students of pesantren were in puberty age. The students of pesantren have a limited access to get periodontal treatment. This study evaluated the effectiveness of control plaque instruction and scaling with hand instrument for the reduction of puberty gingivitis in students of pesantren. The study sample consisted of 61 females aged puberty at a pesantren in Jember. Prior the study, the Plaque Index and Gingival Index were recorded. The sample then received plaque control instructions and scaling with hand instruments. Follow-up exams were made one month after treatment. The data were analyzed by Wilcoxon sign rank test. The Plaque Index and Gingival Index score decrease significantly between baseline and examinations at 30 days (p<0.05). The result showed that plaque control instructions and scaling with hand instruments is efficient to reverse puberty gingivitis. Plaque control instructions and scaling with hand instruments is a simple and inexpensive method of puberty gingivitis treatment in students of pesantren. Key Words: puberty gingivitis, plaque control, scaling